A mixed methods study of health care professionals' attitudes towards vaccination in 15 countries. (December 2022) - Alasmari, Abrar; Larson, Heidi J.; Karafillakis, Emilie
Abstract: Background: Health care professionals are widely considered to be the most trusted source of information on vaccine-related topics. However, several are reporting their own hesitancy around certain vaccines, influencing their intention to vaccinate themselves as well as influencing their recommendations to their patients and target population. Methods: A mixed-methods approach was used including an online survey (n = 1, 504) in 15 countries which aimed to determine drivers of HCPs vaccine confidence and examine how these drivers vary across nations. Thirty in-depth semi-structured interviews were conducted with 10 HCPs in a subset of three countries (France, Greece and Hungry) to explore barriers to HCPs vaccine uptake and their role in addressing vaccine hesitancy among patients. Findings. The survey's regression analysis identified that nurses/midwives and HCPs from Hungary, Italy, Romania and Switzerland were less confident in the safety, importance or effectiveness of vaccines in general. Morocco (35%), Turkey (53%) and Greece (69%) reported the lowest influenza vaccination coverage among HCPs. Morocco also reported the lowest rates of HCPs who were "highly likely" to recommend MMR vaccine (34%), HPV vaccine (31%) and Covid-19 vaccines (29%). More than third of HCPs reported a lack of trust in health authorities and in the information they provide. Thematic analysis revealed that concerns over the risk of side-effects associated with vaccines, preference for natural immunity, whether it was necessary to be vaccinated against influenza every year, not having any chronic disease risk factors, and vaccines mandates as the key barriers to HCPs vaccination against influenza and Covid-19. Conclusion: HCPs have an important role in vaccination and their confidence in vaccination and health authorities must be improved as this may affect their uptake of vaccines and influence their recommendations to their patients. Investigating the impact of political, socio-economic and cultural contexts on concerns about vaccination among HCPs is also necessary.